Kepatuhan Pedagang Kuliner Malam Dalam Penataan Di Kawasan Jln. Ahmad Yani Kota Payakumbuh - Nikella Septiani, Sri; Handini , Dwiyanti (LPPM STISIP IMAM BONJOL, 2024)
This research is about the compliance of night culinary vendors with the city government's regulation on vendor arrangement in Jalan Ahmad Yani Area,Kota Payakumbuh. The government strives to maintain the magnificence and neatness of trading areas through established regulations,on regulation number 09 year 2010. Talcott Parson's social system theory is used in this research. This theory explains that the social system needs to have a clear structure,a system is usually supported by other systems,the system must be able to provide the needs of its actors,and there is participation among members in a system. Moreover,the system must have controls for potential conflicts that would be detrimental. The method used in this research is the qualitative approach with descriptive type. Informants are determined by purposive sampling,a data collection technique with observation,interviews and documentation. Researchers interviewed 16 people: 8 people from the street vendors in Jalan Ahmad Yani area,3 staff from Dinas Pasar (The Market Service),3 buyers,and 2 people from Jalan Sudirman area involved in the Payakumbuh City culinary market. The result shows that the vendors comply with the government's regulations due to several reasons: (1) The regulations have a clear structure, (2) there is support from the relevan agencies (small and medium-sized enterprises), (3) the needs of traders are provided, (4) good cooperation between services, (5) good control from the Market Service, (6) the pleasant attitude from the staffs to vendors. This is influenced by the staff's regulation in dealing with vendors using two methods: (1) Persuasive and (2) repressive